The Price Effect Following Compositional Changes in the FTSE 100 Index - Hadjipierou, Maria (2020)
This thesis investigates the FTSE 100's quarterly index revisions and attempts to capture the impacts of this occurrence on stock prices using data from 2007 until 2021 and an event study methodology. Our analysis is conducted around both the announcement and the event date, and our sample is divided into four time periods. We show that a strong price effect is present for both inclusions and exclusions; a result which supports the presence of an index effect but contradicts the semi-strong form of the EMH. This price effect tends to appear before the events dates, indicating the presence of anticipatory trading. Moreover, an asymmetric price response is documented in the long run. Specifically, a temporary price effect is observed in most periods indicating the support of the Price Pressure Hypothesis. However, during the last two periods, included firms suffered long-term negative abnormal returns; a result which can only be explained by the Price-Volatility Hypothesis. Finally, during the pandemic years, we observe a market overreaction that is accompanied by a delayed response to the announcement news.